Challenges and countermeasures of international economy and trade under the background of big data - Li, Ming (International Journal of Global Economics and Management, 2024)
In the era of big data, international economy and trade are facing unprecedented challenges and opportunities. This paper analyzes the influence of big data on international economy and trade, discusses the related challenges, and puts forward the countermeasures. In terms of challenges, big data brings privacy and security risks, data standardization issues and the widening digital divide. In order to meet these challenges, the international community needs to strengthen data security regulations, formulate international data standards, promote digital inclusion, and improve the transparency of data governance. In addition, this paper also emphasizes the great potential of big data in international trade, including improving market access, reducing trade costs and optimizing supply chain.